Elements of surprise : our mental limits and the satisfactions of plot - Tobin, Vera, 1975- (Harvard University Press, 2018)
Elements of Surprise opens with an novel but narrow focus: how a particular cognitive bias, the "curse of knowledge," underwrites stories that rely on what it calls "well-made surprise," as seen in (for example) classic detective fiction--that is, surprises in novels, films, television, and plays that set us up to be fooled in ways we find pleasing and satisfying. But from there, the book expands its reach. At its core, "cursed" thinking underlies almost everything people write, say, and think about both other people and our own pasts. The more information we have about something, and the more experience we have with it, the harder it is to step outside that experience. What unfolds is both a fresh approach to mental heuristics and biases and an ambitious work of cognitive literary criticism. Elements of Surprise provides a new and exciting way of thinking about the mechanics of narrative, explored through thoughtful readings of classic, popular, and obscure texts.--